PENGGUNAAN NEW AND OLD SEVEN TOOLS DALAM PENERAPAN SIX SIGMA PADA PENGENDALIAN KUALITAS PRODUK STAY HEADREST - Ika Ambar Sari; Merita Bernik (Faculty of Economics and Business, Universitas Malikussaleh, 2018)
The community’s need for transportation from year to year has increased. The high level of automotive industry market absorption is realized by the industries that competition is inevitable. Industries compete with each other to increase their competitive advantage. One aspect from competitive advantage is quality control. This quality control is applied not only to one aspect of management but also to all aspects of the company to create total quality management.To pursue the total quality management, there are quality control tools that are integrated with six sigma approach method that called DMAIC or Define-Measure-Analyze-Improve-Control. Six Sigma itself means a disability of only 3.4 defects per million opportunities. This research was conducted to know the application of quality control with six sigma method at PT Tosama Abadi. Factors causing disability are machine, method, material, human, and environment. By using seven quality control tools integrated with six sigma, it can be seen that the sigma value before the application of six sigma method in the production process at PT Tosama Abadi is 4.12σ with 4340 error from one million opportunity whereas after application, the sigma value is increase to 4.29σ with 2750 DPMO. It shows that defect level is more manageable.